Homogeneous Gas‐Liquid Distribution for Monolithic Structures via a Needle Distributor1. Issue 11 (21st September 2017) - Meitzner, Christine; Hilpmann, Gerd; Schäfer, Thomas; Haase, Stefan; Lange, Matthias; Hampel, Uwe
Abstract: Structured catalysts are a widely discussed approach for process intensification of chemical multiphase reactors. But equal to common catalyst structures, homogeneous educt distribution along the catalytic surface is mandatory for high reactor performance. Especially monolithic structures require a homogeneous initial fluid distribution. A novel distribution concept for gas‐liquid flow through arbitrary channel matrices is presented. It is based on the injection principle where gas and liquid are inserted directly into the channels. A prototype for different cell densities was built and tested by various measurement techniques: gravimetry, X‐ray tomography, and an optical fiber sensor. Additionally, the flow regime per channel was detected as equal to single‐channel conditions. Abstract : The industrial use of monolithic structures as catalyst carriers for three‐phase reactions is still limited to the availability of a gas‐liquid distributor to create the mandatory homogeneous initial distribution. A novel distribution concept for gas‐liquid flow through arbitrary channel matrices is proposed, providing a satisfactory initial condition for intensified multiphase reactions.